2018
DOI: 10.1038/s41419-018-0539-4
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of alternative splicing induced by paclitaxel in human lung cancer

Abstract: Paclitaxel is utilized as the first-line chemotherapeutic regimen for the majority of advanced non-small-cell lung carcinoma. However, whether paclitaxel could suppress cancer progression through modulating RNA alternative splicing remains largely unknown. Here, we demonstrated the effects of paclitaxel on cell proliferation inhibition, cell cycle arrest, and apoptosis. Mechanistically, paclitaxel leads to transcriptional alteration of networks involved in DNA replication and repair, chromosome segregation, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Preliminary investigations revealed that AS perturbation was involved in the initiation and progression of several cancers [ [31] , [32] , [33] ]. In the present study, we identified prognosis-related AS events in ESAD, STAD, COAD, and READ patients.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary investigations revealed that AS perturbation was involved in the initiation and progression of several cancers [ [31] , [32] , [33] ]. In the present study, we identified prognosis-related AS events in ESAD, STAD, COAD, and READ patients.…”
Section: Discussionmentioning
confidence: 99%
“…1D ). According to a recent study [ 16 ], paclitaxel inhibited mitosis by binding to microtubules and regulating mitosis-related pathways, including mitotic nuclear division, chromosome segregation, and G2/M transition of the mitotic cell cycle, in lung cancer cells. The results of our previous study on lung cancer cells showed that paclitaxel upregulated mitosis-related pathways, including mitotic nuclear division and chromosome segregation (unpublished data).…”
Section: Resultsmentioning
confidence: 99%
“…The RNA sequencing results showed that RBM25 was involved in the regulation of multiple splicing events, including exon skipping and intron selection of retention and splice sites. RBM25 inhibits cell proliferation by inducing apoptosis and regulating the cell cycle in multiple cancers ( 31 , 32 ). However, the role of RBM25 in THCA has not been studied.…”
Section: Discussionmentioning
confidence: 99%